COULD HERBAL MEDICINE BE A COMPLEMENTARY THERAPY IN LEUCORRHEA TREATMENT AND CARE? - Zubaeda Zubaeda; Nur Khafidhoh (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The frequency of using the antibiotics and antifungals as a treatment of leucorrhea may cause the bacterial and fungal resistance. Therefore, a treatment is not always optimal and sometimes leads the infection to be worsen. The herbal medicine is needed as an alternative treatment. This study aims to examine the effectiveness of using various herbal medicine in the management of leucorrhea. Methodology: The literature review was conducted in several electronic databases i.e., Google Scholar, Science Direct, and PubMed. The protocol for this study was PRISMA. The keywords such as "herbal medicine" and "leucorrhea" or "vaginal infection" were used to select the literatures. This study only selected the studies conducted during 2000 to 2019, presented in English and used clinical trial research design. Results: This study obtained 10 of 5184 total publications from electronic databases. The publication about herbal medicine for leucorrhea, both of herbal medicine and placebo, herbal medicine compared to conventional medicine and herbal medicine combined with conventional medicine showed that herbal medicine could reduce the symptoms and complaints of leucorrhea which had the ability to be an antimicrobial agent. In contrast, 2 studies revealed the side effects of herbal medicine, i.e., irritation,vomiting, and dry vagina. Conclusion: Herbal medicine was effective as a treatment of leucorrhea and had the prospect to develop as a complementary therapy for treating the leucorrhea. Keywords: Leucorrhea, complementary therapy, herbal medicine